If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=j(-6)
We move all terms to the left:
12-(j(-6))=0
We calculate terms in parentheses: -(j(-6)), so:We get rid of parentheses
j(-6)
We multiply parentheses
-6j
Back to the equation:
-(-6j)
6j+12=0
We move all terms containing j to the left, all other terms to the right
6j=-12
j=-12/6
j=-2
| 8=25000-1500x | | 15-2x=-7x= | | 6(q+12)=12 | | 3(5p-1)-4(3p-7)p=4. | | -x+13=184 | | b18+1=3 | | 6=m•20 | | 7s+12=19 | | 7.2=0.8x | | 1y+18=4y+6 | | 3^(15-5x)=243 | | 5y+180=365 | | 5x+180=365 | | -8=x(2) | | x+5/11=9 | | 4q+8=q+4 | | 2−7w=–10−10w | | y=(-3+-8) | | p14+11=11 | | 5(2n-1)=-7+10n+2 | | 7q+6q+6=9q−10 | | x+9=8+-2x | | 7-8w=-17 | | 9.25=x-2.5 | | e+6=19 | | 5(22n-1)=-7+10n+2 | | 2w+2=2 | | -20=-4(y+6) | | 3^4x-5=(1/7)^2x+10 | | 8a–=a | | 35x70=Mx35 | | 4x–8=36* |